Una storia Polesana . A Story from Pula - Korovljev, Andrej (Factum, 1999)
Duration: 00:28:00 Una Storia Polesana" is a kind of ode dedicated to the simple way of life of "ordinary people". It is also an "homage" to a town that is sinking deeper and deeper into post-communist depression. It tells the stories of the "mahala' - a poor, multicultural community close to the famous Roman Arena tourist landmark in the Croatian coastal town of Pula. The film tells the story of those people who will gradually be forgotten by everybody in the process of nowadays socio-economic development.